Cyber security auditing, assurance, and awareness through CSAM and CATRAM emerging research and opportunities - Sabillon, Regner, 1967- (Information Science Reference, an imprint of IGI Global, 2021)
"This book evaluates the implementation and validation of the Cyber Security Audit Model (CSAM), along with the delivery and inception of the Cybersecurity Awareness TRAining Model (CATRAM) to train personnel on cyber security awareness matter"--